Characterizing ion mobility and collision cross section of fatty acids using electrospray ion mobility mass spectrometry. (27th May 2015) - Zhang, Fang; Guo, Su; Zhang, Manyu; Zhang, Zhixu; Guo, Yinlong
Abstract : This study investigated the ion mobility (IM) and the collision cross section (CCS) of fatty acids (FAs) using electrospray IM MS. The IM analysis of 18 FA ions showed intriguing differences among the saturated FAs, monounsaturated FAs, multi‐unsaturated FAs, and cis ‐isomer/ trans ‐isomer with respect to the aliphatic tail chains. The length of aliphatic tail chain present in the ion structures had a strong influence on the differentiation of drift, while the number of double bond showed a weaker influence. The tiny drift differences between cis ‐isomer and trans ‐isomer were also observed. In the CCS measurements, two internal standards were involved in the mobility calibration and accuracy estimation. It insured our empirical CCS values were of high experimental precision (±0.35% or better) and accuracy (±0.25% or better). Moreover, the mass‐to‐charge ratio ( m/z ) – mobility plots obtained by ion mobility spectrometry with mass spectrometry analysis of FAs – was used to investigate the structural relationship between the molecules. Each series of FAs sharing a similar structure was aligned in the linear plot. Finally, the developed procedure was applied to the determination of FAs in rat adipose tissues, and it allowed the presence of 13 FAs to be confirmed with their exact masses and CCS values. These studies reveal the direct relationship between the behaviors in IM and the molecular structures and thus may provide further validations to the FA identification process. Copyright © 2015 John Wiley & Sons, Ltd.